Optimalisasi Pemasaran Digital Melalui TikTok untuk Pemberdayaan Kampung Digital - Joli Afriany; Suginam; Nurul Ajima Ritonga; Mesran, Mesran (JPM: Jurnal Pengabdian Masyarakat, 2025)
This study aims to examine the impact of a community service program focused on optimizing digital marketing through the TikTok platform on Small and Medium Enterprises (SMEs) in the local area. This program was implemented by involving 20 SMEs who have various types of businesses, such as culinary, handicrafts, and service services. Before the implementation, a survey was conducted to assess the level of participants' understanding of digital marketing, which showed an average understanding result in the range of 2.5 on a scale of 1 to 5. After the program, the post-activity survey showed a significant increase in the average understanding of participants to 4.0. In addition, the average interaction in the content published by participants on social media increased from 20-40 interactions per post to 200-300 interactions. Sales growth reported by participants ranged from 20% to 40%, indicating the success of the program in empowering SMEs to use TikTok as an effective marketing tool. However, challenges related to consistency in creating content and adapting to rapidly changing trends on social media remain identified. Therefore, the need for ongoing support and further training is important to ensure long-term success. The results of this study are expected to provide useful insights for the development of similar programs in the future in supporting local economic growth in the digital era.